2020
DOI: 10.20471/acc.2020.59.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early-Onset Depression after First-Ever Stroke

Abstract: Post stroke depression (PSD) is a severe and frequent stroke complication and one of the crucial factors for the outcome of rehabilitation and life quality after stroke. However, mood disorders frequently remain unnoticed and therefore untreated. The aim of the study was to examine all the potential risk factors and determine the independent predictors of early-onset depression after first-ever stroke, which would help identify high-risk patients, establish early diagnosis and timely treatment that would impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…On one hand, depression could lead to cognitive impairment as we discussed above. Alternatively, with some exceptions [65,66], studies have proposed that cognitive impairment could be the cause, with depression as the consequence [65,67]. One possible explanation is that cognitive improvement associated with lower emotional distress [68] could reduce depression morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, depression could lead to cognitive impairment as we discussed above. Alternatively, with some exceptions [65,66], studies have proposed that cognitive impairment could be the cause, with depression as the consequence [65,67]. One possible explanation is that cognitive improvement associated with lower emotional distress [68] could reduce depression morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that XNJY could treat depression by improving rat body weight, sucrose preference, voluntary activity, and resting time during forced swimming. The quality of life of patients with PSD is significantly lower than that of patients with simple stroke, especially in the fields of cognition, emotion, limb function, and social function [ 27 , 28 ]. PSD and poor neural prognosis may be directly related to neuronal damage or apoptosis after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…); and disease-related factors (stroke site, NIHSS score, hypertension, diabetes, history of hyperlipidemia, etc. ) ( Rabi-Žikić et al, 2020 ; Schöttke et al, 2020 ). Considering so many related risk factors, accurate prediction of PSD tools and early intervention by clinicians is an effective means to improve the prognosis of PSD patients ( Vogel, 1995 ).…”
Section: Introductionmentioning
confidence: 99%